2013
DOI: 10.2478/intox-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poloxamer 407 administration on the serum lipids profile, anxiety level and protease activity in the heart and liver of mice

Abstract: Chronic administration of the poloxamer 407 (P-407), a block copolymer, to elevate serum lipids in mice is a well-established mouse model of hyperlipidemia and atherosclerosis. We tested the hypothesis that the activity of several types of proteases in heart and liver tissue is changed in the early stages of atherosclerosis development. Additionally, we evaluated whether increased serum lipids would induce anxiety in mice, as determined by using a ‘plus-maze’ test. The mice were administered P-407 by intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…This implies that the liver is a direct target for P407 as reported by Cogger et al, [ 32 ], whose findings showed that P407 has a marked effect on the ultrastructure of the liver sinusoidal endothelial cells (LSECs). Necrosis observed in liver tissues also agrees with the findings of Korolenko et al, [ 7 , 9 ]. The liver of atorvastatin treated groups showed moderate infiltration and necrosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This implies that the liver is a direct target for P407 as reported by Cogger et al, [ 32 ], whose findings showed that P407 has a marked effect on the ultrastructure of the liver sinusoidal endothelial cells (LSECs). Necrosis observed in liver tissues also agrees with the findings of Korolenko et al, [ 7 , 9 ]. The liver of atorvastatin treated groups showed moderate infiltration and necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…The advantage with the P407 model is the production of hyperlipidaemia of the hereditary type [ 7 ]. Recent reports have shown the ability of P407 induced hyperlipidaemia to produce early and late stages of atherosclerosis [ 7 - 9 ] and alterations of liver transaminases and plasma proteins in rodents [ 7 - 11 ]. Consumption of synthetic hypolipidaemic drugs have been reported to cause hyperuricemia, diarrhea, nausea, myositis, gastric irritation, flushing, dry skin and abnormal liver function [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this in vivo study, P-407, a non-ionic amphiphilic copolymer, was employed successfully for rapid induction of an acute hyperlipidemia model in rats as well documented in the literature [27,[40][41][42]. Based on the previous outcomes of Pan et al, a single injection of a high dose of P-407 can induce hyperlipidemia, showing lipid peak values 24 hours after injection, without needing treatment repetition [42].…”
Section: In Vivo Studies and Histological Analysesmentioning
confidence: 92%
“…This model has been extensively used in hyperlipidemia research mainly because it produces marked hyperlipidemia (within 24 h) via inhibition of lipoprotein lipase and indirect stimulation of 3-hydroxy-3-methylglutaryl coenzyme A [ 15 , 17 , 20 ]. It should be noted that several reports have shown an absence of poloxamer-induced hepatotoxicity when poloxamer is administered in a single-dose regimen in contrast to the chronic poloxamer 407 model of hyperlipidemia [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. After 1 mg/kg i.p.…”
Section: Introductionmentioning
confidence: 99%